2011
DOI: 10.2337/dc10-2083
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Genes in Epicardial Fat Contiguous With Coronary Atherosclerosis in the Metabolic Syndrome and Type 2 Diabetes

Abstract: OBJECTIVETo determine changes in gene expression in epicardial adipose tissue (EAT) associated with coronary atherosclerosis (CAD) and effects of pioglitazone therapy.RESEARCH DESIGN AND METHODSGenes were quantified by RT-PCR in EAT and thoracic subcutaneous adipose tissue (SAT) obtained during surgery in CAD patients with metabolic syndrome (MS) or type 2 diabetes and control subjects with minimal or no CAD and no MS or type 2 diabetes.RESULTSIncreased expression of interleukin-1 receptor antagonist (IL-1Ra) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(81 citation statements)
references
References 14 publications
4
74
2
1
Order By: Relevance
“…26 The preferential induction of anti-inflammatory cytokines such as IL1RN in SAT could also be a reaction to the enhanced exposure to proinflammatory cytokines in this adipose depot, similar to what has been reported in other conditions of proinflammatory insults in fat, such as type 2 diabetes and obesity. 27,28 Moreover, the induction of IL1RN expression in SAT from patients is consistent with previous reports of the simultaneous recruitment of M2-type macrophages (reparative anti-inflammatory) and M1-type macrophages (proinflammatory) in this adipose depot. 29 Studies on healthy human adipose depots have indicated that the basal level of proinflammatory signaling is higher in VAT, possibly due to the presence of greater numbers of resident immune cells (macrophages, lymphocytes).…”
Section: Discussionsupporting
confidence: 89%
“…26 The preferential induction of anti-inflammatory cytokines such as IL1RN in SAT could also be a reaction to the enhanced exposure to proinflammatory cytokines in this adipose depot, similar to what has been reported in other conditions of proinflammatory insults in fat, such as type 2 diabetes and obesity. 27,28 Moreover, the induction of IL1RN expression in SAT from patients is consistent with previous reports of the simultaneous recruitment of M2-type macrophages (reparative anti-inflammatory) and M1-type macrophages (proinflammatory) in this adipose depot. 29 Studies on healthy human adipose depots have indicated that the basal level of proinflammatory signaling is higher in VAT, possibly due to the presence of greater numbers of resident immune cells (macrophages, lymphocytes).…”
Section: Discussionsupporting
confidence: 89%
“…A host of proinflammatory and proatherogenic adipocyte factors (including TNF-␣, IL-6, MCP-1, nerve growth factor, resistin, leptin, visfatin, and others) have been investigated in relation to coronary atherosclerosis (Table 1) (32,60,99,109,119,121) and have been found to participate in the various stages of atherogenesis (ranging from endothelial dysfunction to plaque destabilization and rupture) (110). The increased visceral adiposity and nutrient stress seen in the metabolic syndrome often disturb the adipocytokine secretion, leading to a chronic inflammatory state, and contribute to the increase in macrophage infiltration into adipose tissue (40,46).…”
Section: Eat Adipocytokines and Their Role In Atherosclerosismentioning
confidence: 99%
“…Given its simple objective measurability, epicardial fat can serve as target for pharmaceutical agents targeting the adipose tissue [1,4]. Thiazolidinediones have been shown to decrease inflammatory cytokines in EAT of patients with type 2 diabetes [14], whereas metformin produced no significant effects [15]. Furthermore, EAT thickness decreased in diabetic subjects treated with atorvastatin in comparison with those who received simvastatin and ezetimibe [16].…”
Section: Introductionmentioning
confidence: 98%